On the Mechanism Underlying Tellurite Reduction by Aeromonas Caviae St Dihydrolipoamide Dehydrogenase - Vasquez-Guzman, C; Arenas-Salinas, F; Cornejo-Leiva, F; Díaz-Vásquez, W (Elsevier, 2014)
The dihydrolipoamide dehydrogenase (LpdA) from the tellurite-resistant bacterium Aeromonas caviae ST reduces tellurite to elemental tellurium. To characterize this NADH-dependent activity, the A. caviae lpdA gene was subjected to site-directed mutagenesis and genes containing C45A, H322Y and E354K substitutions were individually transformed into Escherichia coli ?lpd. Cells expressing the modified genes exhibited decreased pyruvate dehydrogenase, dihydrolipoamide dehydrogenase and TR activity regarding that observed with the wild type A. caviae lpdA gene. In addition, cells expressing the altered lpdA genes showed increased oxidative stress levels and tellurite sensitivity than those carrying the wild type counterpart. The involvement of Cys residues in LpdA s TR activity was analyzed using specific inhibitors that interact with catalytic cysteines and/or disulfide bridges such as aurothiomalate, zinc or nickel. TR activity of purified LpdA was drastically affected by these compounds. Since LpdA belongs to the flavoprotein family, the involvement of the FAD/NAD(P)+-binding domain in TR activity was determined. FAD removal from purified LpdA results in loss of TR activity, which was restored with exogenously added FAD. Substitutions in E354, involved in FAD/NADH binding, resulted in low TR activity because of flavin loss. Finally, changing H322 (involved in NAD+/NADH binding) by tyrosine also resulted in altered TR activity. © 2014 The Authors. Published by Elsevier Masson SAS.